Twelve Ashurbanipal Reliefs - Reade, J. E.
Prince of Wales Museum of Western India, Bombay; Kgl. Glyptothek, München; Archäologisches Institut der Universität Zürich; Staatliche Kunstsammlungen, Dresden; 129-134: Appendix: The original positions of the surviving reliefs.